Rutas Alimentarias: una estrategia de negocios inclusivos que vincula las políticas agrarias y turísticas - Ernesto Barrera; Olivia Bringas Alvarado (Études Caribéennes)
Food Routes are routes that offer tourist services and tourist products that reveal the culture and history of food in areas with special attention to the symbolic meaning of foods and local cultural resources.These routes are the support of a tourism built around local resources. Properly designed, they can participate in rural development. We consider the road food (or gourmet) as an instrument for rural development, food production, resources vernacular culture are at the heart of the territorial project.In Latin America, these initiatives involving rural development and tourism in the context of road maintenance to development since the early 2000s. This article offers a comparative analysis of various development strategies for road food experience around South America, North American and European